KUALITAS PELAYANAN SURAT IZIN MENDIRIKAN BANGUNAN (IMB) PADA BADAN PENANAMAN MODAL DAERAH DAN PELAYANAN TERPADU SATU PINTU (BPMD-PTSP) KOTA PAYAKUMBUH - Diego Aprilino Fourteen; Harapan Tua R.F.S (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Regional Investment Board and One Stop Services (BPMD-PTSP) ofPayakumbuh as places that serve the public, in the service of licensing or nonlicensingis still getting concern by the public of payakumbuh. Convoluted andcomplicated service procedures, the services time often exceeds the provisions,speed and accuracy in providing services to the public. The aim of this researchwas to determine the quality of service and determine the factors that affect thebuilding license service at the Regional Investment Board and One Stop Services(BPMD-PTSP) of Payakumbuh.This research uses the theory by Parasuraman, Zeithhaml, and LeonardBerry in Harbani Pasolong (2007), which consists of Tangible, Reliability,responsivenes, Assurance, Empathy. The method used is qualitative research withdata collection technique through interview, observation and documentation.The results showed that, the quality of building license service at theRegional Investment Board and One Stop Services (BPMD-PTSP) of Payakumbuhis not good enough, there are several dimensions such as physical evidence,reliability, responsiveness, assurance and empathy is not good. From the fifthdimension is only on the assurance dimension that got good judgment, in thisdimension the service provider has been able to provide assurances that theiremployees have skill to take care of the public business, and also have theknowledge to answer and resolve any questions and complaints. As for the otherfour dimensions,the Regional Investment Board and One Stop Services (BPMDPTSP)of Payakumbuh still not meet the quality that public want.Key words: quality, service, building license (IMB)